Η ΕΠΙΔΡΑΣΗ ΤΩΝ ΛΟΙΜΩΝ ΚΑΙ ΤΩΝ ΦΥΣΙΚΩΝ ΚΑΤΑΣΤΡΟΦΩΝ ΤΟΥ ΤΕΛΟΥΣ ΤΟΥ 6ου ΚΑΙ ΤΩΝ ΑΡΧΩΝ ΤΟΥ 7ου ΑΙ. ΣΤΗ ΔΙΑΜΟΡΦΩΣΗ ΤΗΣ ΠΟΛΙΤΙΚΗΣ ΤΟΥ ΑΥΤΟΚΡΑΤΟΡΑ ΜΑΥΡΙΚΙΟΥ - ΣΙΝΑΚΟΣ, ΑΝΑΣΤΑΣΙΟΣ Κ. (Eoa kai Esperia, 2006)
The subject of my paper at the 5th Colloquium of Byzantine Experts ofGreece and Cyprus is the impact of plagues and natural disasters on theEmpire under the rule of Maurice. In particular I refer to the plagues duringthe years of 541-542,558-561, 573-574,588-591 and 599-600, the droughts, thelocust attacks and the famines which followed in 544-549, 552-560, 582, 600-602 and the harsh winter of 601 AD.The sources are explored in order to verify the time at which these eventsoccurred, the places at which they took place and the manner in which theymanifested. The causes underlying them are also explored. According topalaeo-climatologists between 300 and 800 AD the Byzantine Empire regionwent through an extended period of drought, particularly at the end of the 6thcentury AD, the results of which were the famines of 544-549, 552-560, 582,601 and 602 AD. Around the middle of the century there was an increase inrainfall perhaps due to the explosion of the volcano Rabaul which occurred in536 AD1. These alternations in climate conditions (dry - wet - dry) would seemto have been the cause of the outbreak of plague in 541-542 and itsreappearance in 558,573-574,588 and 599. This disease had become epidemic.Following this an attempt is made to explore the results and consequenceswhich arose. The most important were demographic in nature. The epidemicsstruck adolescents to a particularly large degree and thus affected populationrenewal rates leading to a demographic downturn. If this is combined with thedroughts and the famines it is clear that under the reign of Maurice there wasan economic crisis which the Emperor had to attempt to confront andmanage. The economic crisis was a result of the policies adopted by Justinianto re-conquer the western section of the state, which was a major strategic error, which generated financial burdens. Maurice was thus forced to follow alimited economic policy since the economy was vulnerable due to populationand demographic decline. He attempted to reduce domestic expenditure tofinance the needs of his army to face enemies on three fronts, in the East, theWest and in the Balkans (it is possible that the raids by Avars and Slavs fromthe North were related to the droughts and the lack of food) and to create agold reserve. If there were no such reserve the Empire's position as theleading economic power of the time, which could manipulate and settleforeign policy issues with its monetary strength, would be undermined. Hehandled an inherited problem in a forthright manner but his policy was notaccepted, perhaps because it was ahead of its time.This leads us to accept that Maurice was not an avaricious emperor assome historians have portrayed him but a worthy governor who in his effortsto redress the Empire's finances did not give into the pressure of the massesand was thus overturned.